In-situ derived highly active NiS2 and MoS2 nanosheets on NiMoO4 microcuboids via controlled surface sulfidation for high-current-density hydrogen evolution reaction. (1st September 2021) - Yu, Shu Hearn; Gogoi, Pranjal Kumar; Rath, Ashutosh; Dai, Haiwen; Cavin Ng, Zhen Quan; Suenaga, Kazu; Pennycook, Stephen J; Chua, Daniel H.C.
Highlights: In comparison with the conventional chemical vapor deposition (CVD) process, controlled surface sulfidation (CSS) is a more effective approach to tune the physical structure and surface properties of a catalyst. Highly mesoporous nanosheets along with the copious terminal (S2 2− )/unsaturated (S 2− ) species are successfully developed at the edge of MoS2 via CSS, maximally exposing the active sites at the interface. Other than the pyrite-NiS2 and 2H-MoS2, a new and metastable 1T'-MoS2 phase is identified in the CSS samples; this phase is catalytically more active than 2H-MoS2, further boosting the catalytic activity. The as-fabricated noble-metal-free catalyst CSS electrode approaches today's state-of-the-arts performances, which delivers 1Acm −2 at 264 mV with uncompensated structural and catalytic durability. Abstracts: In this work, we highlight the significances of Controlled Surface Sulfidation (CSS) for high-current-density hydrogen evolution reaction (HER) with bimetallic NiMoO4 microcuboids supported on Ni foam. It reveals that a new phase 1T'-MoS2 is derived in-situ from the surface NiMoO4 microcuboids during CSS in addition to pyrite-phase NiS2 and 2H-MoS2 as obtained from full sulfidation. We denote the controlled sulfided sample as "CSS-NiS2 /MoS2 " and the fully sulfided sample as "FS-NiS2 /MoS2 ", respectively. The CSS-NiS2 /MoS2 electrode only required low overpotentials of 12, 47, 112 mV to drive -10, -20, -100 mA cm −2, respectively, which surpasses the FS-NiS2 /MoS2 considerably (54, 90, 195 mV at -10, -20, -100 mA cm −2, respectively). Notably, it delivers a high current density of -500 and -1000 mA cm −2 at low overpotentials of only 200 and 264 mV, respectively. The durability of the high-current-density activity of CSS-NiS2 /MoS2 is also proven over 50 h of stability test. The excellent performances of CSS-NiS2 /MoS2 may be synergistically contributed from the active phases and the design dual hierarchical (i.e., 2D-nano/1D-microhybrids) structure. The CSS may serve as an effective strategy to modulate the electrochemical properties of materials holding great promises for the applications of next-generation energy storage and conversion. Graphical abstract: Image, graphical abstract